Sub-meter-level navigation with an enhanced multi-GNSS single-point positioning algorithm using iGMAS ultra-rapid products - Birinci, Sinan; Saka, Mehmet Halis (Cambridge Univ Press, 2023)
Ultra-rapid products have the advantage of being used in real-time positioning with no external connections. In this study, these products provided by the international GNSS Monitoring and Assessment System (iGMAS) for four global constellations (GPS, GLONASS, Galileo and BDS-3) were assessed in terms of service rate and accuracy in navigation. In this regard, a MATLAB-based in-house code solving the problem was developed for all possible combinations of the constellations. To explore the effectiveness of the iGMAS products, the same dataset has been also processed using GFZ rapid products. The results demonstrate that the GPS and Galileo solutions were substantially comparable to the rapid products concerning service rate and accuracy, but that the GLONASS and BDS-3 iGMAS products require some enhancements. In addition, the Galileo solution produced remarkably good results both individually and in combination. The GPS/GLONASS/Galileo/BDS-3 SPP solution generated a mean root mean square (RMS) error of 0 center dot 54 m horizontally and 0 center dot 89 m vertically. Thus, GPS-only, GLONASS-only, Galileo-only and BDS-3-only solutions were improved by 42%, 79%, 28% and 74% in 3D mean RMS error with the quad system solutions, respectively.
Keywords: precise navigation; iGMAS ultra-rapid products; multi-GNSS SPP